2015
DOI: 10.3136/fstr.21.631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light on the Growth and Acid Protease Production of <i>Aspergillus oryzae</i>

Abstract: Aspergillus oryzae is known to have remarkable potential for the production of secreted enzymes. Submerged (Smf) and solid-state fermentation (SSF) are optimized with regard to temperature, pH, moisture, fermentation time, inoculum concentration, etc. Besides these parameters, the effect of light on growth and its role as a bioprocess variable in controlling enzyme production in A. oryzae is pivotal and hence the subject of study. A. oryzae was shown to be susceptible to light; growth was affected and the vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Based on the monochromatic light sources, our results could bring some thoughts on the previous studies, which used white light sources as research means. The repression in our study is similar to the light response of A. oryzae RIB40 and F6, which produced fewer conidia under a continued white fluorescent light irradiation ( 6 , 17 , 19 ); this may because white light includes the spectrum range of blue light. Besides, the light response of A. oryzae GDMCC 3.31 was not the same as that of the other A. oryzae strains.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Based on the monochromatic light sources, our results could bring some thoughts on the previous studies, which used white light sources as research means. The repression in our study is similar to the light response of A. oryzae RIB40 and F6, which produced fewer conidia under a continued white fluorescent light irradiation ( 6 , 17 , 19 ); this may because white light includes the spectrum range of blue light. Besides, the light response of A. oryzae GDMCC 3.31 was not the same as that of the other A. oryzae strains.…”
Section: Discussionsupporting
confidence: 76%
“… A. oryzae F6, which was obtained after mutagenesis by UV light, formed ring-shaped colonies under the condition of 12 h of light/12 h of dark. In addition, its number of conidia and acid protease were also repressed by continuous white light at an intensity of 25 μmol photon m −2 s −1 ( 19 ). Ten laboratory A. oryzae strains were placed individually under a fluorescent lamp at a light intensity of 25 μmol photon m −2 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…A direct influence of light on acid protease activity has been reported previously for C. unicolor , Phlebia lindtneri and Pycnoporus sanquineus [ 36 ]. In Aspergillus oryzae cells, proteolytic activity showed sensitivity to light and production of respective enzymes was increased in darkness [ 37 ]. It was also found that darkness and constant lighting conditions significantly modified the activity of acid, neutral and alkaline proteases produced by N. crassa [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These same mediums showed that when deproteinization was not inserted previously during the preparation of the culture medium (via protein isoelectric point and continuous flow autoclave process), the enzyme activity significantly decreased to below 85%. Interestingly, Aspergillus oryzae has a known capacity to induce proteases, and consequently can provide amino acids for energy functions (Murthy et al, 2015). Thus, the absence of chemical energy Leandro Freire dos Santos et al from proteins due to the insertion of the deproteinization procedure has promoted high β-galactosidase induction to maintain the energy requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Aspergillus oryzae was evaluated for its ability to induce proteases which could consequently provide amino acids for energy functions (Murthy et al, 2015). Thus, in view of the importance of obtaining β-galactosidase mainly by the induction method (high yields), it was hypothesized that the deproteinization of cheese whey could promote high β-galactosidase induction in order to maintain the chemical energy levels which were previously provided by proteins.…”
Section: Introductionmentioning
confidence: 99%